Application of nanomaterials to enhance microstructure and mechanical properties of concrete - Kwalramani, Manish A; Syed, Z I (International Journal of Integrated Engineering, 2018)
The advances of sustainable construction and the green building movement of the past decade have encouraged comprehensive assessment of building materials and construction practices worldwide.  With superior fire resistance, strength, and a long service life, concrete is the most widely used construction material in the world. Considering the amount of concrete required for various construction works, enhancing sustainability to concrete, both in terms of concrete production and mix design would be a highly desirable prospect. Lately, nanotechnology is a promising field in terms of environmental improvements including energy savings and reduced reliance on non-renewable resources, as well as reduced waste, toxicity and carbon emissions. Nanotechnology allows enhancement of available concrete products by using nano-materials; these nano-materials could be in the form of nano-particles, nano-chemical additives, and nano–fibers in cement-based materials matrix. The usage of nano-materials results in production of concrete with lower volume of cement. The influence of addition of various nano particles such as nano silica, nano Al2O3, nano TiO2, nano Fe2O3, nano clays, and highly dispersed carbon nano tubes in concrete is thoroughly investigated in present work with an initiative towards ‘Green Concrete’ incorporating these waste materials as one of its ingredients